C-Band and O-Band Silicon Photonic Based Low-Power Variable Optical Attenuators - Eslam El-Fiky; Maxime Jacques; Alireza Samani; Luhua Xu; Md. Ghulam Saber; David V. Plant (IEEE Photonics Journal)
We propose and experimentally demonstrate low-power and broadband variable optical attenuators (VOAs) on the silicon photonics platform. The VOAs are based on a Mach–Zehnder interferometer structure. Different variations were fabricated using electron beam lithography using different input and output couplers, heater length and width, operating wavelength, and substrate undercut. Experimental results for the C-band VOA show that, including the substrate undercut, a 3X improvement can be achieved in the power consumption, at the expense of a reduction in electrical bandwidth, where 5- and 20-dB attenuation can be achieved using only 5.5 and 8 mW. Moreover, the VOA can operate over more than 80-nm optical bandwidth with ripples below 1 dB. Furthermore, we study the impact of the heater dimensions on the optical attenuation and VOA bandwidth. Finally, we present similar results for an O-band VOA design.